1983
DOI: 10.1085/jgp.82.6.853
|View full text |Cite
|
Sign up to set email alerts
|

Coupling ratio of the Na-K pump in the lobster cardiac ganglion.

Abstract: The electrogenic Na-K pump coupling ratio in the large neurons of the lobster cardiac ganglion was determined by two different electrophysiological techniques . A graphical analysis plotting exp(E.F/RT) vs .[K]o after the pump was blocked by ouabain was used to determine values for [K]i, PNa/PK, and the pump coupling ratio. These measurements were made 4-8 h after the cells were penetrated with microelectrodes, and thus represent non-Na-loaded steady state values . The value obtained for the pump coupling rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It has been suggested that this stoichiometry is not fixed, depending on internal sodium (Mullin & Brinley, 1969;Gorman & Marmor, 1974), on external potassium (Liberman, 1979) or on external sodium (Livengood, 1983). Lafaire & Schwarz (1986) (1977) it is possible to estimate a net pump flux of 2 7-5 pmol cm-2 s-' (assuming a cell diameter range from 1 to 14 mm), which compares well with our figure; this also falls within values reported in the literature for different systems (Eisner & Lederer, 1980;Cavieres, 1977;Daut & Riidel 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that this stoichiometry is not fixed, depending on internal sodium (Mullin & Brinley, 1969;Gorman & Marmor, 1974), on external potassium (Liberman, 1979) or on external sodium (Livengood, 1983). Lafaire & Schwarz (1986) (1977) it is possible to estimate a net pump flux of 2 7-5 pmol cm-2 s-' (assuming a cell diameter range from 1 to 14 mm), which compares well with our figure; this also falls within values reported in the literature for different systems (Eisner & Lederer, 1980;Cavieres, 1977;Daut & Riidel 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Substituting the current values in eqn (7a) and dividing 'pNa and IpK by Ip yields a ratio of 3/1P8, which compares well with the ratio 3 Na+/2 K+ which has been attributed to the stoichiometry of the sodium pump in many types of cells. It has been suggested that this stoichiometry is not fixed, depending on internal sodium (Mullin & Brinley, 1969;Gorman & Marmor, 1974), on external potassium (Liberman, 1979) or on external sodium (Livengood, 1983). Lafaire & Schwarz (1986) used dihydroouabain to inhibit the sodium pump in full-P. F. COSTA AiND OTHERS grown oocytes of Xenopus.…”
Section: Discussionmentioning
confidence: 99%
“…A refractory period for initiation of DPs is imposed by a combination of the inactivation of 7 Ca by intracellular accumulation of Ca 2+ as well as the increased K + conductance from the Ca 2 + -activation of 7 KCa . When Na + -mediated impulses are present (in non-TTX-treated preparations), a hyperpolarizing current from activation of electrogenic ion transport also contributes to the afterhyperpolarization (Livengood and Kusano, 1972;Livengood. 1983).…”
Section: Characterization Of Four Kinds Of Current In Ligatured Somatamentioning
confidence: 99%
“…It is possible that differences in the prominence of pacemaker potentials in recordings from large cells, even in the same species on the same equipment in the same laboratory (e.g., Tazaki and Cooke, 1979a;Benson, 1980;Berlind, 1982), represent differences in techniques of ganglion isolation or of intracellular electrode penetration. During the hyperpolarization following bursts and the interburst interval, the gradual reduction in conductance to K ' or in hyperpolarizing electrogenic active transport (Livengood and Kusano, 1972;Livengood, 1983) can lead to net depolarization as the balance of currents unmasks an outward injury or "leak" current mediated by nonspecific ionic conductances. The greater prominence of pacemaker potentials in small cells, and thus their role in initiating bursting, may be related merely to their smaller size.…”
Section: Autonomous Rhythmicity: Stretch Responsiveness and Pacemaker...mentioning
confidence: 99%
“…There is, however, reason to believe that there are two sites for K at the outside of the pump, and that a transport cycle can occur when only one of the sites is combined with K (Sachs, 1977;Kropp and Sachs, 1977 ;Livengood, 1983). If such cycles are possible, one can propose a model in which pumps with both activating sites combined with K, pumps with one site bound to K and the other site empty, and pumps with K bound at one site and Na at the other are all capable oftransport, but only the two Na-free species can combine with vanadate .…”
Section: Relationship Of the Site At Which Na Modifies Vanadate Inhimentioning
confidence: 99%